EFFICACY OF CHONDROITIN SULFATE WITH GLUCOSAMINE VERSUS DIACEREIN IN GRADE II AND III OSTEOARTHRITIS KNEE: A RANDOMIZED COMPARATIVE STUDY - R, Mirunalini; M, Chandrasekaran; K, MANIMEKALAI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Osteoarthritis (OA), the most common joint disease has led to great morbidity and disability. Symptomatic slow acting drugs for OA, which includes glucosamine sulfate, chondroitin sulfate, and diacerein provides symptom relief and structure-modifying effects in OA knee. Our aim was to assess the efficacy and safety of chondroitin sulfate with glucosamine versus diacerein in Kellgren-Lawrence Grade II and III OA knee patients. Methods: After approval from Institutional Human Ethics Committee and after getting written informed consent patients were randomized to Group A: Tablet chondroitin sulfate (400 mg) with glucosamine (500 mg) combination thrice a day or Group B: Capsule diacerein 50 mg, twice a day orally both after food. Out of 88 patients screened, 75 of them entered the study. A total of 15 patients failed to complete the study. Remaining 60 patients completed with 30 patients in each group. They were assessed for pain using visual analogue scale (VAS) from baseline and followed-up at 3, 12, 24 weeks. Results: Baseline characteristics in both the groups were matching without any significant difference. At 24 weeks there was reduction in VAS from 6.76 to 1.96 (71.01%) in Group A and from 6.8 to 3.53 (48.09%) in Group B. There was significant difference between the groups with Group A significant over Group B in VAS. Thus, the effect of drug in Group A on pain reduction was greater than Group B. Conclusion: The use of chondroitin sulfate with glucosamine combination resulted in improvement in VAS better than diacerein in OA knee. Keywords: Osteoarthritis, Chondroitin sulfate with glucosamine combination, Diacerein, Visual analogue scale.